Boosting ER-mitochondria calcium transfer to treat Wolfram syndrome - Fischer, Tom Tobias; Nguyen, Lien D.; Ehrlich, Barbara E. (Cell calcium, 2022)
Wolfram syndrome is a rare genetic disorder characterized by endocrine dysfunction and progressive neurodegeneration. By targeting intracellular calcium dysregulations, a sigma-1 receptor agonist rescued neurological deficits in preclinical models of Wolfram syndrome.
Gesehen am 19.07.2022